(untitled) (Geographical Journal of Nepal, 2019)
Depopulation and increasing greenery due to agriculture land abandonment is general scenario in many highlands of Nepal in recent decades. High resolution remote sensing image is used in land use change analysis. Recently, object based image analysis technique has helped to improve the land use classification accuracies using object based image analysis. Thus, this study was carried out with high resolution image data sources and innovative technique of land use classification in the northeast part of Andhikhola watershed, in the Middle Hill of Nepal. Increasing greenery due to agriculture land abandonment in the hill slope is the major land use change. Secondly, increasing built-up area in lowland along the highway is another. Decreasing hill farmers is the major drivers of converting cultivated land into vegetated area and increasing built-up area is due to urbanization and shift of rural people from hill slope to lowland and accessible area. Converting cultivated land into forest, shrubs and grassland is at marginal land and remote areas which is mostly controlled by altitude, slope gradient and slope aspect. Additionally, land suitability and accessibility are also other important controlling factors.